The Prenylflavonoid Xanthohumol Reduces Alzheimer-Like Changes and Modulates Multiple Pathogenic Molecular Pathways in the Neuro2a/APPswe Cell Model of AD - Huang, Xianfeng; Wang, Jing; Chen, Xiao; Liu, Pan; Wang, Shujin; Song, Fangchen; Zhang, Zaijun; Zhu, Feiqi; Huang, Xinfeng; Liu, Jianjun; Song, Guoqiang; Spencer, Peter S.; et al. (Frontiers in Pharmacology, 2018)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that has proved refractory to drug treatment. Given evidence of neuroprotection in animal models of ischemic stroke, we assessed the prenylflavonoid xanthohumol from the Common Hop (Humulus lupulus L) for therapeutic potential in murine neuroblastoma N2a cells stably expressing human Swedish mutant amyloid precursor protein (N2a/APP), a well-characterized cellular model of Alzheimer's disease (AD). The ELISA and Western-blot analysis revealed that Xn inhibited Aβ accumulation and APP processing, and that Xn ameliorated tau hyperphosphorylation via PP2A, GSK3β pathways in N2a/APP cells. The amelioration on tau hyperphosphorylation by Xn was also validated on HEK293/Tau cells, another cell line with tau hyperphosphorylation. Proteomic analysis (2D-DIGE-coupled MS) revealed a total of 30 differentially expressed lysate proteins in N2a/APP vs. wild-type (WT) N2a cells (N2a/WT), and a total of 21 differentially expressed proteins in lysates of N2a/APP cells in the presence or absence of Xn. Generally, these 51 differential proteins could be classified into 7 main categories according to their functions, including: endoplasmic reticulum (ER) stress-associated proteins; oxidative stress-associated proteins; proteasome associated proteins; ATPase and metabolism-associated proteins; cytoskeleton-associated proteins; molecular chaperones-associated proteins, and others. We used Western-blot analysis to validate Xn-associated changes of some key proteins in several biological/pathogenic processes. Taken together, we show that Xn reduces AD-related changes in stably transfected N2a/APP cells. The underlying mechanisms involve modulation of multiple pathogenic pathways, including those involved in ER stress, oxidative stress, proteasome molecular systems, and the neuronal cytoskeleton. These results suggest Xn may have potential for the treatment of AD and/or neuropathologically related neurodegenerative diseases.